BUSANA ISLAMI: KESEIMBANGAN ANTARA MODESTISME DAN KREATIVITAS FASHION - Nurirvan, Sopi; Indana Sulfa, Fadhila; Citra Ayu, Laela; Praja Gumulya, Saskia; Parhan, Muhamad (IAIN Bone, 2024)
Discourses that talk about the concept of ethical dress in Islam have become a crucial part of providing the doctrine of religious values in Islam. Nowadays, in general, Muslim women tend to wear the hijab as a means of fulfilling their obligations, but do not pay attention to and understand the ethics of dressing in Islam itself. Muslim women's fashion faces the challenges of developing fashion trends which continue to develop in this millennial era. The aim of this article is to understand and explain how the adaptation of Muslim fashion is an illustration of the balance of modestism with currently developing fashion trends and creativity. The method used is a qualitative approach using a case method/interview methods and literature studies. Along with Islamic law, the findings of this research show that even though millennial Muslim women already know how to dress according to Islamic rules and recommendations, they are still unable to practice or apply these rules and recommendations. Millennial Muslim women still dress according to environmental trends and do not follow Islamic rules and recommendations. This research allows us to explain modestism in Muslim fashion and how to collaborate Muslim fashion with fashion trends which are currently developing very rapidly. This can be used to measure how well Muslim women understand clothing trends and the balance between modernism and current fashion trends.Â